Computer-based instruction and learning of secondary mathematics - Tabajen, Malvin Rivera (2006)
The research experimented on the use of Computer-based Instruction or CBI in the learning of secondary mathematics of three different groups of learners classified as high, average and low achievers in mathematics. Three first year classes were used and undertook the CBI in mathematics. Findings that revealed differences between the posttest and the pretest serves within each group and between groups seemed to indicate that CBI could be used effectively to facilitate classroom instruction.
Thesis (M.A. Educational Technology)--University of the Philippines, Diliman.
Keywords: Mathematics -- Philippines -- Quezon City -- Computer-assisted instruction; Mathematics -- Study and teaching (Secondary) -- Philippines -- Quezon City